2014
DOI: 10.1155/2014/750398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treated Silicon Dioxide Nanoparticles on Some Mechanical Properties of Maxillofacial Silicone Elastomer

Abstract: Current materials used for maxillofacial prostheses are far from ideal and there is a need for novel improved materials which mimic as close as possible the natural behavior of facial soft tissues. This study aimed to evaluate the effect of adding different concentrations of surface treated silicon dioxide nanoparticles (SiO2) on clinically important mechanical properties of a maxillofacial silicone elastomer. 147 specimens of the silicone elastomer were prepared and divided into seven groups (n = 21). One con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 29 publications
3
61
0
Order By: Relevance
“…The matrix and the bottom parts and the cover of the mold were previously coated with petroleum jelly (12,16) for HTV silicone elastomer molds and separating medium for RTV silicone elastomer molds, then the matrix parts and bottom parts were securely attached for the two types molds (metal molds for HTV silicone elastomer and acrylic molds for RTV silicone elastomer) and placed on the vibrator for RTV silicone elastomer with the mold spaces coated with separating medium The material was injected from the syringe into the mold and a cover (RTV silicone molds) and a glass slab (HTV silicone molds), was laid onto the matrix filled with the material. Lying of the cover part, the glass slab was started from one side by resting the bottom edge of the slab and holding the topedge, while the covers, the glass slab was carefully and slowly lowered onto matrix to force excess material and air out ahead of it.…”
Section: Pouring the Mixture Into The Moldsmentioning
confidence: 99%
See 2 more Smart Citations
“…The matrix and the bottom parts and the cover of the mold were previously coated with petroleum jelly (12,16) for HTV silicone elastomer molds and separating medium for RTV silicone elastomer molds, then the matrix parts and bottom parts were securely attached for the two types molds (metal molds for HTV silicone elastomer and acrylic molds for RTV silicone elastomer) and placed on the vibrator for RTV silicone elastomer with the mold spaces coated with separating medium The material was injected from the syringe into the mold and a cover (RTV silicone molds) and a glass slab (HTV silicone molds), was laid onto the matrix filled with the material. Lying of the cover part, the glass slab was started from one side by resting the bottom edge of the slab and holding the topedge, while the covers, the glass slab was carefully and slowly lowered onto matrix to force excess material and air out ahead of it.…”
Section: Pouring the Mixture Into The Moldsmentioning
confidence: 99%
“…Then, samples were conditioned at a standard laboratory temperature of 23±2°C for a minimum of 3 hours after removal of flash (43) . The flash was removed with a scalpel and sharp surgical blade # 11 (12) .…”
Section: Conditioning Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study followed and found the addition of intrinsic silicone pigments significantly influenced dynamic mechanical properties of the silicone elastomer tested over low frequencies from 0.5 to 2.5 Hz . Furthermore, incorporation of surface‐treated SiO 2 nanoparticles at 3% concentration enhanced overall mechanical properties of A‐2186 …”
Section: Resultsmentioning
confidence: 99%
“…These closed paths provide the coherent feedback mechanism [28][29][30]. The scatterers within the laser media contribute in trapping light photons due to multiple scattering; in doing so, the light path inside these media will be long (long time interval), and this is one reason for a decrease in the threshold intensity [31,32].…”
Section: Introductionmentioning
confidence: 99%